Eksistensi Ruko dan Relevansi Desainnya Dalam Perkembangan Bisnis di Kawasan Heritage, Gajah Mada, Denpasar - I Komang Gelda Manika Aprizio; Pande Putu Dwi Novigga Artha; A. A. Ngurah Agung Candra Gupta; Nyoman Andy Armawan (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2023)
Cultural heritage areas provide insights that correlate with the historical value of the area. Historical value characterizes the uniqueness of the area and influences the physical development of the city in general. The city's past civilization is the main attraction. The tourism perspective offers a paradigm shift in society and tourists' thinking. The cultural heritage area of Jalan Gajah Mada Denpasar is a reflection of the ancient city of Denpasar today. The Gajah Mada area is surrounded by old buildings that function as shops. Shop houses (ruko) in the Gajah Mada cultural heritage area have existed since the 1920s and began to be built massively in the 1970s. Until now, around 312 shophouses have been located along Jalan Gajah Mada, Jalan Sulawesi, and Jalan Kartini. In this study, through interviews, observation, and analysis, the existence and relevance of shophouses (ruko) along Jalan Gajah Mada, Jalan Sulawesi, and Jalan Kartini were obtained. This study took 8 samples to find out which building was chosen, namely based on location (Gajah Mada Street, Sulawesi Street, Kartini Street), building function (food and beverage, coffee shop, fabric shop, etc.), and number of floors (2 floors, 3 floors, and 4 floors).